Animation maths : campus handbook - De Pauw, Ivo, 1971-; Masselis, Bieke, 1978- (Tielt : Lannoo, 2021)
In effective animation programming, one must be able to rely on theoretical knowledge as well as research-based insights in applicability. This updated version of Animation Maths contains an overview of both. In addition to exploring collision detection, it also puts forward a discussion of programmable kinematics. These physics of motion, designed to complement programming, offer an invaluable tool in adding realism to games and animations. Furthermore, screen effects and image handling are taken to a professional level by a detailed outline of all the basic transformations. The uniqueness of this book lies in its calculus-free approach. In order to cover the basics of the discipline, Animation Maths contains a brief summary of the fundamentals in arithmetics, solving systems and trigonometry. Animation Maths is accompanied by the website www.animationmaths.be which contains online support and useful downloads.